The Factors Affecting the Efficiency of Online Learning During the Situation of COVID-19 Undergraduate Students in Chonburi - Kerdjaroenporn, Thunyathorn; Mimgkhwan, Yamonporn; Khamyoo, Waranya; Noypune, Sununwadee; Tangpattanakit, Jaruporn (Journal of Humanities and Social Sciences, Rajapruk University, 2023)
The objectives of this research was to study the factors affecting the efficiency of online learning during the situation of COVID-19 of undergraduate students in Chonburi. A questionnaire was administered to 420 undergraduate students in Chonburi. The statistical analysis data were frequency, percentage, average, standard deviation, Simple Linear Regression Analysis and Multiple Linear Regression Analysis. The findings of the research were as follows: The flexible learning, interaction, tension, and responsibility influence the efficiency of online learning for undergraduate students in Chonburi. The relationship test found that flexible learning can be a mediator between tension and online learning efficiency for undergraduate students in Chonburi with a statistically significant at .05 level. The availability of media and equipment and learning environment are not efficient for online learning undergraduates in Chonburi.